Formulasi dan Evaluasi Sediaan Nano-Gel Minyak Atsiri Daun Nilam (Patchouli oil) Menggunakan HPMC Sebagai Gelling Agent - Marhammah, Natasya Putri; Maharini, Indri; Elisma, Elisma; Rabbani, Haiga Hatthaya; Saputri, Sindi; Mulia, Zulaikha Permata; Afriana, Nadila (Jurnal Pelayanan Kefarmasian dan Sains, 2025)
Background: Acne vulgaris is a chronic inflammation of the pilosebaceous unit characterized by clinical signs of non-inflammatory and inflammatory lesions with varying degrees of inflammation, often caused by bacterial infection. Patchouli plant (Pogostemon cablin Benth) is a notable source of essential oil with antibacterial properties. Enhancing the effectiveness of essential oil as an anti-acne agent can be achieved through the development of a nanogel formulation.Objective: To formulate a nanogel containing patchouli leaf essential oil and evaluate its activity against Propionibacterium acnes.Methods: The formulation of patchouli leaf essential oil nanoemulsion was carried out with varying concentrations of patchouli oil at 1.5%, 2%, and 2.5%. The evaluation of the nanoemulsion included particle size analysis, zeta potential testing, and emulsion type determination. The resulting nanoemulsion was then formulated into a nanogel using HPMC as the gelling agent. The physical evaluation of the nanogel included organoleptic tests, homogeneity tests, viscosity tests, pH measurement, spreadability tests, adhesion tests, stability tests, irritation tests, and antibacterial activity tests. Data analysis was performed descriptively, followed by statistical analysis using One-Way ANOVA with a 95% confidence levelResults: The patchouli leaf essential oil (Patchouli Oil) nanoemulsion with concentrations of 1.5%, 2%, and 2.5% met the criteria for nanoemulsion formulation. The nanogel preparations in F1, F2, and F3 were solid in form, yellowish-white in color, had the characteristic aroma of patchouli leaf essential oil, and were homogeneous, meeting the requirements for gel formulations and stable. Conclusion: The formulation of nanogel containing patchouli leaf essential oil (Patchouli Oil) meets the requirements for a good gel preparation.